Effect of Chronic Periodontitis on Oxidative Status in Patients With Psoriasis and Psoriatic Arthritis. Issue 5 (1st May 2016) - Sezer, Ufuk; Şenyurt, Süleyman Ziya; Gündoğar, Hasan; Erciyas, Kamile; Üstün, Kemal; Kimyon, Gezmiş; Kırtak, Necmettin; Taysı, Seyithan; Onat, Ahmet Mesut
Abstract : Background: Psoriasis (PS), psoriatic arthritis (PsA), and chronic periodontitis (CP) are the most common chronic inflammatory diseases and have remarkable pathologic similarities. The aim of this study is to investigate the effect of periodontal inflammation on oxidative stress in patients with PS and PsA by evaluating serum total antioxidant status, total oxidant status, oxidative stress index, levels of lipid hydroperoxides, and the activities of paraoxonase, arylesterase, and ceruloplasmin. Also measured were the levels of prolidase and total sulfhydryl groups. Methods: A total of 120 participants were divided into six groups of 20 participants: 1) PS with CP (PS‐CP); 2) PS‐periodontally healthy (PS‐C); 3) PsA with CP (PsA‐CP); 4) PsA‐periodontally healthy (PsA‐C); 5) systemically healthy with CP (CP); and 6) both systemically and periodontally healthy (C). Demographic, periodontal, and serum oxidative parameters were evaluated. Results: Oxidative stress index values of PS‐C, PS‐CP, PsA‐C, and PsA‐CP groups were approximately twice as high as those of C and CP groups, and there were no differences between any of the PS (PS‐C and PS‐CP), and PsA (PsA‐C and PsA‐CP) groups. Total antioxidant status levels of the C group were higher by 27% compared with those of the PS‐C and the PsA‐CP groups ( P <0.05). Total oxidant status levels of both PsA‐C and PsA‐CP groups were approximately twice as high as those of the C ( P <0.05) and CP ( P <0.05, P <0.001 respectively) groups. Conclusions: The contribution of CP on systemic oxidative levels in patients with PS and PsA or systemically healthy individuals seems limited. PS and PsA did not show any additional detrimental effect on clinical parameters in patients with CP.